NATIONALISM AND ITS IMPACT ON INTERNATIONAL RELATIONS – A REVIEW (International Journal of Food and Nutritional Sciences, 2023)
This study explores the Impact of Nationalism on International Relations. Nationalism exerts a profound influence on international relations, shaping the behavior of states and the dynamics of global politics. At its core, nationalism emphasizes the primacy of national identity, sovereignty, and independence, asserting a nation-state's right to self-determination and autonomy. This ideology has historically driven movements for decolonization, state formation, and resistance against external interference. In international relations, nationalism impacts various aspects, including conflict resolution, diplomacy, economic policies, and global governance. Nationalist rhetoric and aspirations frequently drive states to assert their interests assert their interests aggressively on the global stage, sometimes leading to tensions and even conflicts between nations. For example, nationalist ideologies have historically been linked to territorial disputes, wars of independence, and regional instability. Moreover, nationalism can influence economic policies through protectionist measures and trade policies aimed at preserving domestic industries and jobs. Such measures can strain international trade relations and contribute to economic conflicts. Culturally, nationalism fosters pride in national heritage and traditions, influencing how states engage with global cultural dynamics and international institutions. However, it can also fuel resistance to globalization and international norms, challenging universal standards of human rights and international law. Despite its potential for conflict, nationalism also plays a constructive role in international relations by fostering solidarity and unity within states and providing a basis for diplomacy and cooperation. Nations often form alliances based on shared nationalist ideologies or security concerns, contributing to stability in regional and global contexts. In conclusion, nationalism is a complex and multifaceted phenomenon that significantly shapes contemporary international relations. Its impact spans from the assertion of state sovereignty to economic policies and cultural diplomacy. Understanding nationalism's influence is crucial for navigating global challenges and promoting peaceful cooperation among nations in the increasingly interconnected world.